Studi Review dalam Meningkatkan Hasil Belajar di Sekolah Dasar dalam Sebuah Penelitian Tindakan Kelas - Lailatuz Zahroh; Indryani; Hadiyanyo (Universitas Muhammadiyah Kuningan, 2025)
This research aims to review the influence of Classroom Action Research (PTK) on student learning outcomes at elementary school (SD) level. The method used in this research is a literature review study, by collecting and analyzing scientific articles related to the implementation of PTK in elementary schools. The data collection technique used is analysis, which will later function to collect relevant data and sources in this research. The type of data used is qualitative, chosen because the method applied is a literature study. From analysis of various sources, it was found that the implementation of CAR had a significant impact in improving student learning outcomes. This method allows teachers to identify learning problems, plan improvements, and evaluate the effectiveness of teaching strategies implemented on an ongoing basis. This study combines six literature studies with a Systematic Literature Review (SLR) approach to examine the influence of the Card Sort, Problem-Based Learning (PBL), Jigsaw, Course Review Horay, and Guided Discovery learning methods on achieving learning outcomes. The results of the analysis show that interactive and collaborative methods, such as Card Sort, Jigsaw, and PBL, are able to increase student participation, understanding, and learning motivation. Meanwhile, the influence of social media on learning outcomes emphasizes the important role of parents and teachers in guiding the use of social media to remain productive. Overall, active and collaborative learning methods and improvements to improve the quality of learning at the basic level.